Nanoencapsulation of Essential Oil: A Tailored System of Green Therapeutic Potential - Arora, Shefali; Chhetri, Sukanya; Bhandari, Pankaj (Current Topics in Medicinal Chemistry, 2025)
Essential oils (EOs) are at the forefront of the pharmaceutical industry today and have been rekindled as natural drugs with innovative techniques. However, many factors related to their volatility and deterioration can be captured by encapsulation. The nanoencapsulation of EO is a novel development to protect EOs from environmental factors in order to retain their biochemical and pharmacological properties, thus leading toward sustainable health advancement. Nanoencapsulation of essential oil (EO) is a fascinating technique to solve the instability problem of EOs in the presence of light, air, moisture, and temperature variations. In addition to this, this process ensures safer handling with controlled release, along with improved efficacy and bioavailability. This review outlines the most outstanding methods for the nanoencapsulation of EOs and their mechanism of action against disease pathogenesis.
Keywords: nanoemulsion